Search for flavor-changing neutral current B meson decays in p(p)over-bar collisions at root s=1.8 TeV - Abe, F; Akimoto, H; Akopian, A; Albrow, MG; Amendolia, SR; Amidei, D; Antos, J; AnwayWise, C; Aota, S; Apollinari, G; Asakawa, T; Ashmanskas, W; et al. (1996)
We report on a search for the flavor-changing neutral current decays B d,s 0 → μ+μ-, B+ → μ+μ-K+ and B0 → μ+μ-K*0 using data from pp̄ collisions at √s = 1.8 TeV, collected with the Collider Detector at Fermilab during the 1992-1993 running period. We find no indication of such decays, and we set the following 90% confidence level upper limits on branching ratios: B(B0 → μ+μ-) < 1.6 × 10-6, B(BS 0 → μ+μ-) < 8.4 × 10-6, B(B+ → μ+μ-K+) < 1.0 × 10-5, and B(B0 → μ+μ-K*0) < 2.5 × 10-5.